Love over gold and mind over matter? Identifying capabilities that preserve medical assistants' sustainable employability - Bram P. I. Fleuren; Alden Yuanhong Lai; Lynda Gruenewald-Schmitz; Jennifer Larkin; Christina T. Yuan (BMC, 2024)
Abstract Background Medical assistants (MAs) are crucial for affordable, high-quality primary care, but what motivates this low-wage occupational group to stay in their job remains underexplored. This paper identifies the work aspects that MAs value ("capabilities"), and how they affect sustainable employability, which refers to employees' long-term ability to function and remain in their job. Methods We used structural equation modelling to assess how capabilities relate to four outcomes among MAs: burnout, job satisfaction, intention to quit, and experiencing work as meaningful. Results We find that earning a good income, developing knowledge and skills, and having meaningful relationships at work relate to the outcomes. Meaningful relationships represent a stronger predictor than salary for one's intention to quit. Conclusions Competitive salaries are necessary but not sufficient to motivate low-wage health care workers like MAs to stay in their job. Health care leaders and managers should also structure work so that MAs can foster meaningful relationships with others as well as develop competencies.